Biodegradable Foam dari Bonggol Pisang dan Ubi Nagara sebagai Kemasan Makanan yang Ramah Lingkungan (Biodegradable Foam Derived from Musa acuminate and Ipomoea batatas L. as an Environmentally Friendly Food Packaging) - Chairul - Irawan; Aliah aliah; Ardiansyah Ardiansyah (Jurnal Riset Industri Hasil Hutan, 2018)
Biodegradable foam is a packaging material intended as a substitute for styrofoam. Materials used in this study were mahuli banana (Musa acuminata) stem and nagara tubers (Ipomoea batatas L) with aim to find out the best composition material for the best physical characteristics of biodegradable foam. Prior to use in the process of making biodegradable foam, mahuli banana stem and nagara tuber were firstly pulverized to a size of 100 mesh. Then, the mahuli banana stem and nagara tubers powders were mixed with compositions of 60:40, 70:30, and 80:20; and as controls pure material was utilized. Another treatment was the addition of PVA (polyvinyl alcohol) as much as 10%v/v and no addition of PVA (UNPVA). The process of making biodegradable foam began with plasticizing on a hotplate at 150oC for 3 minutes, thermopressing, and drying in a microwave. The biodegradable foam (bio-foam) characteristics were tested with DSC and SEM as well as for its hardness and biodegradation. Based on the results of hardness test, DSC, SEM and biodegradation, the best physical characteristic was obtained from 60:40 composition with the addition of PVA. The hardness test of bio-foam with PVA and UNPVA was 4.02 MPa and 3.59 MPa, respectively. The melting point of bio-foam with the addition of PVA was 166.50 oC with heating flow of -12.38 MW whereas the melting point of bio-foam without UNPVA addition was 166.45 oC with heating flow of -16.07 MW. The result of SEM test showed that bio-foam mixed with PVA had a smaller pore compared to UNPVA. The structure of bio-foam with a smaller pore produced biodegradable foam with higher compressive strength. Biodegradation test results showed that both samples were completely degraded after ± 2 months of being deposited in the soil.